Evaluating systemic immune-inflammation index for in-hospital and long-term mortality in elderly non-ST elevation myocardial infarction patients. (3rd October 2022) - Orhan, A L; Saylik, F; Cicek, V; Akbulut, T; Selcuk, M; Cinar, T
Abstract: Introduction: This investigation aimed to evaluate the predictive value of systemic immune-inflammation index (SII) for in-hospital and long-term mortality in elderly patients with non-ST elevation myocardial infarction (NSTEMI). Methods: In this retrospective investigation, 314 consecutive elderly patients who were diagnosed with NSTEMI in a tertiary center were included. The SII was computed as neutrophils x platelets/lymphocytes. Based on the increased SII values, we classified the research sample into three tertile groups as T1, T2, and T3. The in-hospital and long-term mortality were defined as the primary outcomes. Results: Patients in the T3 group had lower chances to survive both in the in-hospital and long-term periods as compared to those in the T2 and T1 groups. The SII was independently related with in-hospital (HR: 1.001, 95% CI: 1.000–1.1003, p=0.038) and long-term mortality (HR: 1.004, 95% CI: 1.002–1.006, p<0.001) according to the multivariable Cox regression models. To predict long-term mortality, the optimal value of the SII was >2174 with 80% sensitivity and 85.4% specificity. When the AUC values of the SII, neutrophil/lymphocyte ratio (NLR), and platelet/lymphocyte ratio (PLR) were assessed to predict long-term mortality, the SII had the greatest value (AUC: 0.862), followed by the NLR (AUC: 0.731) and the PLR (AUC: 0.698). Additionally, combining SII with the traditional risk factors and the Charlson Comorbidity Index revealed a significant improvement in C-statistics. Conclusion: This might be the first investigation to demonstrate that the SII was independently linked with in-hospital and long-term mortality in elderly NSTEMI patients. Funding Acknowledgement: Type of funding sources: None.